Point-of-care ultrasound for diagnosis of Phlegmasia Cerulea Dolens asociated to abdominal aortic aneurysm - Jorge Giraldo; Elizabeth Cordoba; Katherinne Santa; Diego Abreo (Revista de Educación e Investigación en Emergencias, 2023)
Phlegmasia Cerulea Dolens (PCD) is a rare condition that carries a high morbidity risk if misdiagnosed in the emergency department. Point-of-care ultrasound (POCUS) helps to make the diagnosis timely, leading to earlier life and limb saving treatment. PCD is associated with hypercoagulable states, but can be precipitated by trauma and is more common in the setting of neoplasia.